2016
DOI: 10.1371/journal.pone.0155273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pioglitazone in Preventing In-Stent Restenosis after Percutaneous Coronary Intervention in Patients with Type 2 Diabetes: A Meta-Analysis

Abstract: BackgroundThe benefits of pioglitazone in patients with type 2 diabetes mellitus (T2DM) after percutaneous coronary intervention (PCI) is unclear.ObjectivesTo evaluate the effect of pioglitazone on prevention of in-stent restenosis (ISR) in patients with T2DM after PCI.MethodsAll full-text published relevant studies compared the effect of pioglitazone with control group (placebo or no pioglitazone treatment) on ISR in patients with T2DM after PCI were identified by searching the databases including PubMed, EMB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…All these factors could interfere with the effect of pioglitazone for reduced MACCEs. On the other hand, pioglitazone's effect in lipid lowering via regulation of adipogenesis remained intact in ESRD patients [16,29], which could be supported by our observation that patients with underlying dyslipidemia benefit more from pioglitazone rather than DPP4-inhibitors.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…All these factors could interfere with the effect of pioglitazone for reduced MACCEs. On the other hand, pioglitazone's effect in lipid lowering via regulation of adipogenesis remained intact in ESRD patients [16,29], which could be supported by our observation that patients with underlying dyslipidemia benefit more from pioglitazone rather than DPP4-inhibitors.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, numerous studies among PPAR-γ showed its potential role in the treatment of cardiovascular disease [16,[22][23][24]. These were compatible with the outcome trial and observation study of pioglitazone [21,[25][26][27][28][29][30][31]. However, it is of some concern in the population with advanced renal impairment, due to the side effect of fluid overload and the risk of bone loss and congestive heart failure [9,18,21,31,32].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Metformin, a biguanide, has shown to reduce infection rates 8 . Sulfonylureas may increase the risk of death following coronary angioplasty, whereas thiazolidinediones seem to be have no effect 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Rosiglitazone and pioglitazone currently are commercially available. Previous meta-analysis have demonstrated benefits of both TZDs and pioglitazone in prevention of ISR and target lesion revascularization (TLR) 8 12 . Few of these analyses are based on RCT data; the results of these studies are also inconsistent.…”
Section: Introductionmentioning
confidence: 99%